Effect of Chandrasoor (Lepidium sativum) supplementation on performance of crossbred sows along with nursing piglets - G.P. LAKHANI, BISWAJIT ROY (Indian Journal of Animal Production and Management, 2019)
The present study was conducted at Pig Farm, Livestock Farm, Adhartal, College of Veterinary Science& A.H., NDVSU, Jabalpur. A total of 14 crossbred sows (Large white yorkshire X Desi) just after farrowingwere randomly assigned to two different groups (Control and Chandrasoor), with seven sows in each group.Individual sows along with piglets were maintained at farrowing pen. All the sows were fed the same gestationdiet during gestation. Diets were formulated as per ICAR (2013) standard. After the farrowing, sows of theChandrasoor group received 30 g Chandrasoor seed powder daily. Rest of the managemental schedulewas same for both the groups Piglets were weaned at 42 days of age. Significant differences (P